2008
DOI: 10.1002/cd.218
|View full text |Cite
|
Sign up to set email alerts
|

Bridging identities and disciplines: Advances and challenges in understanding multiple identities

Abstract: The chapters in this volume address the need for a better understanding of the development of intersecting identities over age and context. The chapters provide valuable insights into the development of identities, particularly group identities. They highlight common processes across identities, such as the role of contrast and comparison and the need for individual effort in identity formation. They suggest the value of studying multiple identities in interaction and using interdisciplinary approaches. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
1
27
0
1
Order By: Relevance
“…Hal ini menggambarkan bahwa mereka telah mengambil keputusan mengenai pilihan karier yang sesuai dengan minat dan kemampuan berdasarkan informasi yang diperoleh sebelumnya. Remaja akhir mampu mencapai level tertinggi dalam mengintegrasikan berbagai dimensi identitas karena mereka lebih mampu berpikir rasional dan mengambil keputusan yang tepat, serta memiliki lebih banyak pengalaman (Boyes & Chandler, 1992;Phinney, 2008).…”
Section: Diskusiunclassified
“…Hal ini menggambarkan bahwa mereka telah mengambil keputusan mengenai pilihan karier yang sesuai dengan minat dan kemampuan berdasarkan informasi yang diperoleh sebelumnya. Remaja akhir mampu mencapai level tertinggi dalam mengintegrasikan berbagai dimensi identitas karena mereka lebih mampu berpikir rasional dan mengambil keputusan yang tepat, serta memiliki lebih banyak pengalaman (Boyes & Chandler, 1992;Phinney, 2008).…”
Section: Diskusiunclassified
“…Along these lines, research has suggested that the process of acculturating into a mainstream national culture may lead to decreases in ethnic identity (Amiot et al., 2007; Lambert, 1977; Lambert & Taylor, 1983; Noels & Clement, 1996). However, other lines of work also suggest that, while balancing different identities may be a challenging task of adolescence and emerging adulthood, specific group identities need not be conflictual (Cross & Cross, 2007; Frable, 1997; Howard, 2000); and more specifically, national identity need not be in conflict with ethnic identity, especially in the context of a pluralistic society (Berry, 1997; Berry et al., 2006; Phinney, 2008; Verkuyten, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for more empirical study that contextualizes how REI is dependent on, and yet distinct from, identity development related to gender, social class, birth cohort, and other important influences (Phinney, ). For example, it might be that racial/ethnic centrality, exploration, and/or commitment can constrain exploration of identity related to social class or to locality (e.g., being a citizen of a certain city or region) when it promotes alienation from other groups or reinforces justification for dominance of one group over another.…”
Section: Integration Of Rei Research: Identity and Contextmentioning
confidence: 99%
“…Although there are multiple studies that examine associations between REI and outcomes by social group factors like gender (e.g., Chavous, Rivas‐Drake, Smalls, Griffin, & Cogburn, ), understanding of REI differences between boys and girls might be advanced by focusing instead on the associations between REI and gender‐identity development and their interdependence in explaining functioning (e.g., do concurrent changes in ethnic and gender centrality predict well‐being or behavior?). Phinney () recommends longitudinal studies of co‐occurring identity‐development processes but acknowledges the challenges of this approach, given that the key dimensions and theoretical frameworks for different social group identities (e.g., REI and gender identity) are often defined in ways that are not necessarily compatible. Unlike research that adopts a singular focus, longitudinal studies on identity intersections could promote understanding of REI as one part of identity development and permit consideration of the interrelation to other aspects of identity.…”
Section: Integration Of Rei Research: Identity and Contextmentioning
confidence: 99%